Phenotypic and Molecular Detection of Extended Spectrum Beta-Lactamases Producing-Bacteria Isolated From Pregnant Women With Genital Tract Infection in Duhok Governorate - Nerway, Sozan M.; Al-Delaimi, Muna S. (Science Journal of University of Zakho, 2021)
Beta-lactamase producing bacteria have a worldwide distribution with a high degree of prevalence in both community and hospital. Furthermore, multidrug resistant (MDR) and extended spectrum β-lactamases (ESBL) producing bacterial isolates from women patients may limit treatment options available. This study was designed to determine the frequency of bacterial isolates associated with genital tract infection in pregnant women and their antimicrobial resistance profile and to assess the prevalence of extended spectrum β-lactamases producing bacteria. Demonstrating the β-lactamase genes (blaTEM, blaSHV and blaCTX-M) by using polymerase chain reaction (PCR) assay with specific primers, was carried out on patients who were admitted to Maternity and Obstetric Hospital in Duhok city from November 2018 to October 2019. A total of 100 high vaginal swabs were collected from pregnant women patients between the ages 18-45 years. All clinical samples were cultured and standard microbiological methods were used to identify bacterial isolates, then confirmed by Vitek®2 compact automated system. All gram negative bacterial isolates were studied phenotypically and genotypically for extended spectrum β-lactamases-production. Out of 100 vaginal swabs, 88% confirmed positive culture; 90.9% of which were bacterial isolates. From the total bacterial isolates, 38.8% were gram negative bacteria, with a predominant 54.8% Klebsiella pneumoniae followed by Escherichia coli 35.5%. 54.8% of the isolates were characterized as multidrug resistance isolates, 29% isolates were extensive drug resistance, and no pan drug resistance were detected. Among these, the commonest extended spectrum β-lactamases producing isolates were Escherichia coli 81.8% followed by, Klebsiella pneumoniae 58.8%. Extended spectrum β-lactamases-producing isolates have showed significantly higher resistance than non- extended spectrum β-lactamases producing isolates to third and fourth generation cephalosporins. CTX-M was the most common β-lactamase gene 73.7% among extended spectrum β-lactamase producing strains, followed by blaSHV, 57.9% and blaTEM 52.6%, 21.1% had combination of all bla genes, 15.8% had CTX-M only and combination of blaCTX-M with blaSHV and blaTEM. 10.5% among extended spectrum β-lactamases producing isolates carried SHV type only and in combination with TEM type while TEM gene were observed in 5.3%. We concluded that the drug resistant isolates were common, worryingly high and it may limit treatment options available. In this study a high level of the blaCTX-M gene was demonstrated among extended spectrum β-lactamases producing isolates.
Keywords: Vaginal Infection; Pregnant Women; MDR; XDR; ESBL; Iraq